Implementation of Lecturer Communication Strategies in Building Student Understanding of PTNBH at the Bandung Institute of Technology (ITB) West Java - Dindin Saepudin (MANAZHIM, 2023)
The purpose of this study is to determine the communication strategy of lecturers in building understanding of PTNBH at the Bandung Institute of Technology. Communication is a fundamental thing in human life, even communication becomes a phenomenon for the formation of a society or community integrated by information, where each individual in the society itself shares information sharing to achieve common goals. In simple terms, communication can occur if there is a similarity between the person who conveys the message and the person who receives the message. The research method that researchers use is a descriptive research method with a qualitative type through historical methods, namely research that studies a principle that occurs in the present and in the past based on the traces obtained. As a result of the research that has been carried out, it can be concluded that the things behind ITB implementing its public communication strategy are in building a common understanding of various matters related to the change in the status of PTN to PTN-BH. The institution, in this case the ITB Public Relations, carries out interaction activities through a public communication strategy where everyone can respond to each other and monitor the situation so that a common understanding of the background of changes in the status of the institution is formed; The public communication strategy is also carried out in reducing and providing solutions to the unrest that occurs in the ITB academic community. In this study, stakeholders focused on ITB students Departing from intense interactions, various integrated habits of all ITB academics were constructed to achieve common goals (success)